PENGARUH STIMULUS VISUAL TERHADAP AKTIVITAS OTAK: PENDEKATAN BIOPSIKOLOGI - Lusinta Rehna Ginting; Husna Astria Aritonang; Kezia Irene Caroline Sitorus; Graciana Estercordia Waruwu; Kirana Permata Daris Naibaho (Jurnal Bilqolam Pendidikan Islam, 2025)
Visual stimuli are one of the primary sensory stimuli that play a significant role in influencing brain activity and human behavior. From a biopsychological perspective, visual stimuli are not only processed as sensory input but also involve complex neurophysiological mechanisms and psychological processes. This study aims to analyze the influence of visual stimuli on brain activity and its implications for individual perception, emotion, and behavior. The research method used was a literature review, examining various scientific sources including books, national and international journal articles, and relevant research reports. The results of the study indicate that visual stimuli are processed through an organized visual nervous system, involving the primary visual cortex and association areas, and are influenced by cognitive factors such as attention, experience, and emotion. Visual stimuli have been shown to enhance attention, motivation, creativity, and adaptive behavioral responses, particularly in learning contexts. Therefore, the appropriate use of visual stimuli can be an effective strategy in supporting cognitive function and individual psychological well-being.